An analysis of metacognitive awareness in reading strategies to comprehend academic text among English Education students at Universitas Negeri Padang - Ivanka. S, Syafiq Laura; Addinna, Ainul (Journal of English Language Teaching, 2025)
Reading academic texts requires more than understanding vocabulary; it also involves the ability to plan, monitor, and evaluate one’s reading process. This study aimed to analyze the level of metacognitive awareness in reading strategies among English Education students at Universitas Negeri Padang and to identify the types of strategies they most frequently used. The research employed a quantitative descriptive design. The data were collected through the Metacognitive Awareness of Reading Strategies Inventory-Revised (MARSI-R) questionnaire and semi-structured interviews. The participants were 24 fourth-year students selected through purposive random sampling, with six students interviewed to gain deeper insights. The results revealed that students generally demonstrated a medium level of metacognitive awareness (M = 3.4). Among the three strategy categories, problem-solving strategies were most frequently used (M = 3.6), followed by support strategies (M = 3.4) and global strategies (M = 3.2). This finding indicates that while students were fairly aware of how to manage their reading, they did not consistently plan or monitor their comprehension. Overall, students tended to apply strategies unconsciously, highlighting the need for greater emphasis on metacognitive awareness training in reading instruction to develop more strategic and independent readers.